2020
DOI: 10.1371/journal.pone.0243551
|View full text |Cite
|
Sign up to set email alerts
|

Why women with breast cancer presented late to health care facility in North-west Ethiopia? A qualitative study

Abstract: Background Although early diagnosis is a key determinant factor for breast cancer survival, delay in presentation and advanced stage diagnosis are common challenges in low and middle income countries including Ethiopia. Long patient delays in presentation to health facility and advanced stage diagnosis are common features in breast cancer care in Ethiopia but the reasons for patient delays are not well explored in the country. Therefore we aimed to explore the reasons for patient delay in seeking early medical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 36 publications
2
11
0
7
Order By: Relevance
“…The mortality rate is comparable to that of other regions of the continent and significantly higher than that of the majority of developed countries [ 1 , 3 ]. The age-standardized BC mortality rates in East Africa and Ethiopia are 17.9 per 100,000 women and 22.9 per 100,000 women, respectively [ 1 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The mortality rate is comparable to that of other regions of the continent and significantly higher than that of the majority of developed countries [ 1 , 3 ]. The age-standardized BC mortality rates in East Africa and Ethiopia are 17.9 per 100,000 women and 22.9 per 100,000 women, respectively [ 1 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although early diagnosis is a key determinant factor for breast cancer survival, delay in presentation and advancedstage diagnosis are common challenges in developing countries. [17] The majority of patients (62.16%) in our study presented at late stage (III and IV). This can be attributed…”
Section: Discussionmentioning
confidence: 68%
“…Unsar et al [36] showed that esophageal cancer not only imposes physical and psychological burdens on patients but also gradually increases family caregivers' anxiety and depression as the caregiving burden increases. Moreover, income levels are considered a crucial infuencing factor for patients to actively seek medical care [37][38][39]. In the case of esophageal cancer as a chronic disease, expensive follow-up treatment can place a heavy fnancial burden on families, leading to delays in seeking medical help or poor treatment adherence [40,41].…”
Section: Discussionmentioning
confidence: 99%